Compensation of thermal nonlinear effect in hybrid microsphere resonators. (1st September 2014) - Xie, Chengfeng; Cui, Danfeng; Tang, Jun; Shang, Chenglong; Zhang, Tianen; Xue, Chenyang; Liu, Jun
Abstract : A hybrid structure with higher linearity to compensate the thermal refraction effect based on a ruby microsphere resonator is proposed and has been realised. The thermal refractive effect of the hybrid structure is theoretically and experimentally demonstrated, which showed that it is limited by the diameter of the resonator and the Q factor. By increasing the diameter, the transmission spectrum experiences a transition from blueshift to redshift induced by thermal absorption and when it is equal to a specific value the thermal refraction effect can be reduced or even eliminated. Experiments showed that there is no shift with varying input optical power since the thermal refraction of ruby can be completely compensated at the diameter of the microsphere d = 1.5 μm and Q = 2.3 × 10 6 when the KD‐310 coated thickness is 60 μm. This reported work shows that the structure could be used to improve stability and is sensitive in high‐ Q resonators for applications in laser, biosensor and nonlinear optics.